Legal Status Options in the Legitimation of Out-of-Wedlock Children in Mixed Marriages - Murtadho, Nazhif Ali (Fakultas Hukum Universitas Islam Jakarta, 2025)
Mixed-nationality marriages between Indonesian citizens and foreign nationals create legal uncertainty for children born out of wedlock regarding citizenship, inheritance rights, and property ownership. This study aims to analyze the mechanisms of adoption, acknowledgment, and legitimation and their implications for legal certainty and the protection of children’s rights. Employing a normative doctrinal method with statutory and conceptual approaches, the research draws on primary and secondary legal materials. Our findings reveal that the legal status of children born out of wedlock depends on the validity of the parents’ marriage and paternal acknowledgment: the Civil Code (KUHPerdata) provides erkenning and legitimation mechanisms to secure inheritance rights, while Law No. 12/2006 and Ministerial Regulation No. 10/2023 allow for limited dual citizenship following formal acknowledgment, though practical implementation remains hindered by administrative and procedural obstacles. We conclude that formal paternal acknowledgment is an absolute prerequisite for ensuring children’s identity, citizenship, and civil-law rights; therefore, regulatory harmonization and simplification of administrative procedures are needed to prevent statelessness and guarantee non-discrimination in accordance with the best-interests-of-the-child principle.